Validity of stem cell-loaded scaffolds to facilitate endometrial regeneration and restore fertility: a systematic review and meta-analysis - Huang, Qiao-yi; Zheng, Hui-da; Shi, Qi-yang; Xu, Jian-hua (Frontiers in Endocrinology, 2024)
Objective Various stem cell-loaded scaffolds have demonstrated promising endometrial regeneration and fertility restoration. This study aimed to evaluate the efficacy of stem cell-loaded scaffolds in treating uterine injury in animal models.The PubMed, Embase, Scopus, and Web of Science databases were systematically searched. Data were extracted and analyzed using Review Manager version 5.4. Improvements in endometrial thickness, endometrial glands, fibrotic area, and number of gestational sacs/implanted embryos were compared after transplantation in the stem cell-loaded scaffolds and scaffold-only group. The standardized mean difference (SMD) and confidence interval (CI) were calculated using forest plots.Thirteen studies qualified for meta-analysis. Overall, compared to the scaffold groups, stem cell-loaded scaffolds significantly increased endometrial thickness (SMD = 1.99, 95% CI: 1.54 to 2.44, P < 0.00001; I² = 16%) and the number of endometrial glands (SMD = 1.93, 95% CI: 1.45 to 2.41, P < 0.00001; I² = 0). Moreover, stem cell-loaded scaffolds present a prominent effect on improving fibrosis area (SMD = -2.50, 95% CI: -3.07 to -1.93, P < 0.00001; I² = 36%) and fertility (SMD = 3.34, 95% CI: 1.58 to 5.09, P = 0.0002; I² = 83%). Significant heterogeneity among studies was observed, and further subgroup and sensitivity analyses identified the source of heterogeneity. Moreover, stem cell-loaded scaffolds exhibited lower inflammation levels and higher angiogenesis, and cell proliferation after transplantation.The evidence indicates that stem cell-loaded scaffolds were more effective in promoting endometrial repair and restoring fertility than the scaffold-only groups. The limitations of the small sample sizes should be considered when interpreting the results. Thus, larger animal studies and clinical trials are needed for further investigation.